Cadmium fractionation in soils affected by organic matter application: Transfer of cadmium to cacao (Theobroma cacao L.) tissues - Gutiérrez, Eduardo; Chávez, Eduardo; Gamage, Kasuni H. H.; Argüello, David; Galkaduwa, Madhubhashini B.; Hettiarachchi, Ganga M. (Frontiers in Environmental Science, 2022)
Elevated cadmium (Cd) concentration in cacao (Theobroma cacao L.) beans have concerned chocolate consumers worldwide because of the potential detrimental human health effects. Applying organic amendments to reduce Cd availability in soils and its translocation to cacao plants has gained increased attention. Compost application on soil surface could modify the labile Cd in soils and yet could enhance Cd bound to humic and fulvic acids, forming an organo-metallic complex that could reduce the availability of Cd to plants. This study investigated the effect of surface compost applications at two rates, the chemistry and fractionation of Cd at two soil depths, and the relationship of these soil Cd pools with plant uptake. The research was carried out in four Ecuadorian cacao farms, three of them located in Manabí and one located in Guayas provinces. In all farms, the organic matter was applied at two rates. The low rate consisted of 6.25 Mg ha-1 and the high rate 12.5 Mg ha-1. There was also a control treatment with no compost application. All treatments were applied in a completely randomized block design with three replicates per farm. Soil samples were collected at two depths, surface and below surface, at several equidistant points around the trunk. Leaf samples composed of up to 20 mature-age leaves around the canopy, and healthy and ripe cacao pots were collected from each treatment. Soil Cd was fractionated into five pools i.e., KNO3- (exchangeable), H2O- (sorbed), NaOH- (organic bound), EDTA- (carbonate bound), and HNO3- (residual) fractions, using a sequential extraction procedure. Cadmium bound to fulvic acids and humic acids in soils were also extracted separately. The EDTA-extractable fraction showed the highest concentration of Cd at the two depths. Cadmium bound to fulvic acids showed the highest concentration in organic matter treatments in all farms with respect to the control (p < 0.05). Plant-Cd were negative and significantly correlated with the Cd extracted by EDTA, NaOH, HNO3, and FA-Cd pools. The process of mobility of Cd in soils cultivated with cacao, based on plant uptake, was strongly associated with chemical characteristics, especially pH and SOC.